Fermentation of Broiler Chicken Manure to Overcome Flies in Selulung Village, Kintamani, Bangli, Bali - Astiti, Ni Made Ayu Gemuh Rasa; Radu, Valentin; Sulistyawan, Dedhy; Amblayasa, Anak Agung Bagus; Kartana, I Wayan; Situmeang, Yohanes Parlindungan; Mahardika, Ida Bagus Komang (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This applied research aims to evaluate the effectiveness of the fermentation of broiler chicken manure as a method of fly control in Selulung Village, Kintamani, Bangli, Bali. The broiler chicken manure fermentation method involves mixing chicken manure with other ingredients, including microorganisms from EM4 and cow manure that has been left for one month, and water to dissolve molasis. The mixture is then fermented for three months. The results of the service show that the fermentation of broiler chicken manure as citrus plant fertilizer can reduce the number of flies around the garden and the surrounding environment. In addition, the fermentation of broiler chicken manure can also reduce unpleasant odors and improve environmental quality. The result demonstrates that fermenting a mixture of 1 part chicken manure and husk, 1 part cow manure, 0.01 part EM4, and 0.01 part molasses, dissolved in 0.05 parts water, can be an effective and environmentally friendly method for controlling flies in Selulung Village. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 6: Clean Water and SanitationSDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and Production SDG 13: Climate ActionSDG 15: Life on Land